The Effect of Using the Role-Play Strategic approach on the Vocabulary Development of the Beginner Level Learners in the Arabic Language Teaching Unit for Non-Native Speakers at Qassim University - Al-Sultan, Muhammad Sultan Ali; Daif-Allah, Ayman Sabry (Dirasat: Human and Social Sciences, 2024)
Objectives: Vocabulary is an essential component of communication in any language. Learners of Arabic as a second language encounter difficulties in learning vocabulary due to the use of traditional methods. Therefore, the research aims to identify the effect of using the role-play strategy on the vocabulary development of the beginner level learners in the Arabic Language Teaching Unit for Non-Native Speakers at Qassim University. Methods: The study used the quasi-experimental approach, and it was administered to twenty-six learners, thirteen learners for the experimental group and a similar number for the control group. The experimental group was taught by role-play strategy, and the control group was taught by traditional methods. Data were collected by using a vocabulary test. Results:.The results of the study show extremely statistical significant differences in the mean scores of the control and experimental group learners in the post administration of the vocabulary test in favor of experimental group learners. The tabulated T value is 1.782 with 12 degrees of freedom and a significant level (p=0.011). The average score and the standard deviation of the learners in the experimental group is (0.73±47.53), whereas the average score and the standard deviation of learners in the control group is (1.96±19.69). Conclusions: The study recommends expanding the use of role-play strategy in teaching the Arabic language skills to learners of Arabic as a second language.